The effects of a commercially available botanical supplement on strength, body composition, power output, and hormonal profiles in resistance-trained males - Kreider Richard; Willoughby Darryn; Campbell Bill; Foster Cliffa; Bushey Brandon; Poole Chris; Taylor Lem; Wilborn Colin (Taylor & Francis Group, 2010)
Abstract Background Fenugreek (Trigonella foenum-graecum) is a leguminous, annual plant originating in India and North Africa. In recent years Fenugreek has been touted as an ergogenic aid. The purpose of this study was to evaluate the effects of Fenugreek supplementation on strength and body composition. Methods 49 Resistance trained men were matched according to body weight and randomly assigned to ingest in a double blind manner capsules containing 500 mg of a placebo (N = 23, 20 ± 1.9 years, 178 ± 6.3 cm, 85 ± 12.7 kg, 17 ± 5.6 %BF) or Fenugreek (N = 26, 21 ± 2.8 years, 178 ± 6 cm, 90 ± 18.2 kg, 19.3 ± 8.4 %BF). Subjects participated in a supervised 4-day per week periodized resistance-training program split into two upper and two lower extremity workouts per week for a total of 8-weeks. At 0, 4, and 8-weeks, subjects underwent hydrodensiometery body composition, 1-RM strength, muscle endurance, and anaerobic capacity testing. Data were analyzed using repeated measures ANOVA and are presented as mean ± SD changes from baseline after 60-days. Results No significant differences (p > 0.05) between groups were noted for training volume. Significant group × time interaction effects were observed among groups in changes in body fat (FEN: -2.3 ± 1.4%BF; PL: -0.39 ± 1.6 %BF, p < 0.001), leg press 1-RM (FEN: 84.6 ± 36.2 kg; PL: 48 ± 29.5 kg, p < 0.001), and bench press 1-RM (FEN: 9.1 ± 6.9 kg; PL: 4.3 ± 5.6 kg, p = 0.01). No significant interactions was observed among groups for Wingate power analysis (p = 0.95) or muscular endurance on bench press (p = 0.87) or leg press (p = 0.61). In addition, there were no changes among groups in any clinical safety data including lipid panel, liver function, kidney function, and/or CBC panel (p > 0.05). Conclusion It is concluded that 500 mg of this proprietary Fenugreek extraction had a significant impact on both upper- and lower-body strength and body composition in comparison to placebo in a double blind controlled trial. These changes were obtained with no clinical side effects.